Brain resting‐state networks in adolescents with high‐functioning autism: Analysis of spatial connectivity and temporal neurodynamics. Issue 2 (17th January 2018) - Bernas, Antoine; Barendse, Evelien M.; Aldenkamp, Albert P.; Backes, Walter H.; Hofman, Paul A. M.; Hendriks, Marc P. H.; Kessels, Roy P. C.; Willems, Frans M. J.; de With, Peter H. N.; Zinger, Svitlana; Jansen, Jacobus F. A.
Abstract: Introduction: Autism spectrum disorder (ASD) is mainly characterized by functional and communication impairments as well as restrictive and repetitive behavior. The leading hypothesis for the neural basis of autism postulates globally abnormal brain connectivity, which can be assessed using functional magnetic resonance imaging (fMRI). Even in the absence of a task, the brain exhibits a high degree of functional connectivity, known as intrinsic, or resting‐state, connectivity. Global default connectivity in individuals with autism versus controls is not well characterized, especially for a high‐functioning young population. The aim of this study is to test whether high‐functioning adolescents with ASD (HFA) have an abnormal resting‐state functional connectivity. Materials and Methods: We performed spatial and temporal analyses on resting‐state networks (RSNs) in 13 HFA adolescents and 13 IQ‐ and age‐matched controls. For the spatial analysis, we used probabilistic independent component analysis (ICA) and a permutation statistical method to reveal the RSN differences between the groups. For the temporal analysis, we applied Granger causality to find differences in temporal neurodynamics. Results: Controls and HFA display very similar patterns and strengths of resting‐state connectivity. We do not find any significant differences between HFA adolescents and controls in the spatial resting‐state connectivity. However, in the temporal dynamics of this connectivity, we did find differences in the causal effect properties of RSNs originating in temporal and prefrontal cortices. Conclusion: The results show a difference between HFA and controls in the temporal neurodynamics from the ventral attention network to the salience‐executive network: a pathway involving cognitive, executive, and emotion‐related cortices. We hypothesized that this weaker dynamic pathway is due to a subtle trigger challenging the cognitive state prior to the resting state. Abstract : In light with current literature, adolescents with (high‐functioning) autism did not show significant spatial differences in their resting‐state networks (in location and strength of activation) when compared with healthy controls. However, using Granger causality, they appear to be impaired in the dynamics, in terms of causality, between two essential resting‐state networks involving emotion‐, social‐, as well as central executive‐related cortices (or functional areas of the brain). This suggests the importance of analyzing not only spatial functional network connectivity, but rather their temporal dynamics, to better understand the neural functioning of autism.